Capital Structure and Profitability of a Comparative Study on Government and Joint Venture Banks in Nepal - Mukhiya, Ramesh (A Bi-annual South Asian Journal of Research & Innovation, 2025)
The study intends to look into how capital structure affects the Nepalese Government and the Joint Venture Bank's profitability. The statistical analysis of the study includes the secondary data. Using software for analysis, a descriptive and causal comparative analysis has been conducted by gathering data from bank websites and using correlations and multiple regression models for hypothesis testing. Out of the entire population, 2 Government and 3 joint venture banks have been taken as a sample for the study. The capital structure and profitability have been investigated as a cause-and-effect relationship using a causal comparative research design. In this study, NIM is used as a dependent variable, and leverage ratio, bank size, liquidity ratio, and capital ratio are independent variables. As a statistical tool, the following tools are used: mean, standard deviation, correlation, multiple regression model, and hypothesis testing. Excel and SPSS are both used to evaluate those variables. Leverage Ratio and bank size have a negative and significant impact on NIM in Nepal's government banks. The Liquidity Ratio shows an insignificant and positive effect on NIM. The capital ratio has a significant and favourable impact on the NIM of government banks. Whereas the Leverage Ratio has an insignificant positive impact on the NIM of Joint Venture Banks. Bank Size has a significant negative relation with NIM. Liquidity Ratio shows a significant and positive relation with NIM. Capital ratio has an insignificant negative impact on the NIM of Joint Venture Banks. However, Banks should value the significance of other variables.